The growth of muscles in rams of the edilbaevskoy breed during moderate growing up and fattening - D V Nikitchenko; V E Nikitchenko; R D Ibragimov (RUDN Journal of Agronomy and Animal Industries, 2010)
A study of muscle growth was carried out on newborn sheep of the edilbaevskoy breed aged 3, 7, 10, 12,5- months old under moderate rearing and fattening. It was established that muscles grow most intensively up till 7 months age in lambs. Muscle increase takes place unevenly according to anatomical regions. The absolute weight of trunk muscles in 12,5 months old compared to newborn lambs increases by 10.68 times, muscles of fore limbs by 7,63 times, muscles of hind limbs by 9.21 times, that brings to a change in their ratio. For instance, the relative weight of muscles of the abdominal walls increases from 5.45% (in newborn) to 8,91%; muscles of the shoulder girdle increase from 13.41% to 14,43%; muscles of fore limbs decrease from 17,56% to 13,91%; muscles of hind limbs decrease from 35,22% to 34,17% respectively. The distribution of muscular mass into different parts of the limbs depends on the genetic program of morphogenesis and character of distribution of functional loading; thus, the more proximal the group of muscles, the higher is the rate of growth and multiplication of weight increase.